PENGENALAN MEREK, PERSEPSI KUALITAS, HARAPAN KONSUMEN DAN INOVASI PRODUK TERHADAP KEPUTUSAN MEMBELI DAN DAMPAKNYA PADA LOYALITAS KONSUMEN (Studi Kasus: Produk Batik Sutra Halus Merek Tamina) - *, Tamamudin (IAIN Pekalongan, 2012)
This study aimed to examine the effect of brand awareness, perceived quality, customer expectations and product innovation on buying decisions and on increasing customer loyalty. Structural Equation Modeling (SEM) based on AMOS was employed to test the hypotesis.The results showed that brand awareness has positive and significant impact on purchasing decisions, perceived quality has positive and significant impact on purchasing decisions, consumer expectations have a positive and significant impact on purchasing decisions, product innovation have a significant and positive impact on purchasing decisions and buying decisions have positive and significant customer loyalty.